Potret Perkembangan Kewirausahaan di Kalangan Generasi Muda - Hasan Anshori; Kamil Shefta Mufasir Ulum; Octavia Citrananda; Ari Anggarani Winandi Prasetyoning Tyas (As-Syirkah: Islamic Economic & Financial Journal, 2025)
Youth entrepreneurship has gained increasing attention in Indonesia’s economic development, particularly in the era of digitalization and globalization. This article aims to provide an overview of the development of entrepreneurship among young people by examining its trends, opportunities, driving factors, challenges, and contributions to the national economy. The study employs a literature review of academic sources, official reports, and recent data on youth entrepreneurship and the creative economy sector. Findings indicate that the advancement of digital technology, social media, and startup ecosystems has fostered the emergence of new business innovations that are not only profit-oriented but also emphasize social values and sustainability. Key driving factors include family support, government initiatives, and inspiration from successful young entrepreneurs. Nevertheless, several obstacles remain, such as limited access to capital, lack of managerial experience, underdeveloped entrepreneurial skills, and insufficient regulatory support. Despite these challenges, young people play a strategic role in strengthening Indonesia’s creative economy sector, creating jobs, enhancing local value, and promoting sustainability principles. With appropriate policies and a more inclusive entrepreneurial ecosystem, youth have the potential to become the main drivers of the nation’s economic growth.